East-West Dialogue - Chen, Lujun; Pohl, Karl-Heinz (Springer Nature, 2023)
This Open access book is a collection of interviews published by China News Service, a Beijing-based news agency, in its "West-East Talk" column. It has been divided into five sections: "Mutual Learning Among Civilizations," "Hot Issues," "About China," "Sino-U.S. Relations" and "Cultural Collision". The interviews are with more than 50 eminent scholars, scientists, politicians, authors, etc., from different parts of the world as well as China, who have an association with China and see the real China beyond the stereotypes. Besides current global issues, the book also covers Chinese culture, history as well as China-U.S. relations, described as one of the most important bilateral relationships in the world today. The book aims to build a platform for dialogue among different civilizations and appreciate the "harmony within diversity" of different cultures, especially of the East and West. We hope it will foster tolerance and rationality, dispelling the misconceptions about China in particular.